Death penalty instructions to jurors : still not comprehensible after all these years - Stygall, Gail (Language and Law / Linguagem e Direito, 2017)
This paper describes and analyzes the unrevised, current state of death penalty pattern jury instructions in the state of Washington. With comparisons to the findings of the Capital Jury Project, this study examines why the death penalty instructions are even more difficult than the ordinary, difficult to understand US pattern jury instructions. The concept of mitigation presents particular problems, with jurors misunderstanding the instruction, misapplying it or ignoring it. As mitigation is the alternative to aggravation and a death penalty verdict, this problem is critical. In addition, as Judith Levi (1993) found in the Illinois death penalty pattern jury instructions, the instructions in general point to a default position for death. Washington’s pattern jury instructions for death penalty cases are as difficult to comprehend as both pattern jury instructions in general and death penalty instructions in particular.